Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Pendidikan - Saleh, Khairul (FENOMENA, 2014)
The leadership of school headmasters is a key factor which determines the quality of education in the school, so that the educational process can be well-planned, sytematic, and professional. The school headmasters, in running his/her leadership to manage the school, should pay attention on the improvement of the teachers’ quality.  it is because the teachers who are face to face to the students directly. The improvement of the teachers’ quality will affect the students’ achievement. That is why, a good qualified school headmasters will always ask, persuade, lead, guide, and push the teachers to teach professionaly to reach the educational goals. In fact, leadership of the school headmasters has not run well to create a good teaching process and the quality of education